The Effect of Intraoperative Methadone Compared to Morphine on Postsurgical Pain: A Meta-Analysis of Randomized Controlled Trials - Mark C. Kendall; Lucas J. Alves; Kristi Pence; Taif Mukhdomi; Daniel Croxford; Gildasio S. De Oliveira (Anesthesiology Research and Practice)
Background and Objectives. Methadone is commonly used in chronic pain, but it is not frequently used as an intraoperative analgesic. Several randomized studies have compared intraoperative methadone to morphine regarding postsurgical analgesia, but they have generated conflicting results. The aim of this investigation was to compare the analgesic efficacy of intraoperative methadone to morphine in patients undergoing surgical procedures. Methods. We performed a quantitative systematic review of randomized controlled trials in PubMed, Embase, Cochrane Library, and Google Scholar electronic databases. Meta-analysis was performed using the random effects model, weighted mean differences (WMD), standard deviation, 95% confidence intervals, and sample size. Methodological quality was evaluated using Cochrane Collaboration’s tool. Results. Seven randomized controlled trials evaluating 337 patients across different surgical procedures were included. The aggregated effect of intraoperative methadone on postoperative opioid consumption did not reveal a significant effect, WMD (95% CI) of −0.51 (−1.79 to 0.76), (P=0.43) IV morphine equivalents. In contrast, the effect of methadone on postoperative pain demonstrated a significant effect in the postanesthesia care unit, WMD (95% CI) of −1.11 (−1.88 to −0.33), P=0.005, and at 24 hours, WMD (95% CI) of −1.35 (−2.03 to −0.67), P<0.001. Conclusions. The use of intraoperative methadone reduces postoperative pain when compared to morphine. In addition, the beneficial effect of methadone on postoperative pain is not attributable to an increase in postsurgical opioid consumption. Our results suggest that intraoperative methadone may be a viable strategy to reduce acute pain in surgical patients.